1988
DOI: 10.1182/blood.v72.1.299.bloodjournal721299
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous antigen expression in B lineage acute lymphoblastic leukemia

Abstract: Cell surface phenotypes of 113 B lineage acute lymphocytic leukemia (ALL) cases, defined by the presence of HLA-DR and at least one B-cell- specific antigen (either CD19, CD20, or CD22), were compared with antigen-defined stages of normal B lymphocyte development. The cases were first evaluated for expression of HLA-DR, CD19, CD34, CD10, CD20, and CD22 by indirect one-color immunofluorescence. Pairwise comparisons of cell surface marker expression were performed for each leukemic sample: no correlations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
21
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 0 publications
5
21
0
Order By: Relevance
“…Cytoplasmic CD22 was a better marker than surface CD22 expression, which was generally weaker and on a lower proportion of cells. Other investigators have reported contradictory results of surface membrane labeling of CD22 in precursor-B ALL, ranging from negative to positive in the majority (4,8). Our results are more in keeping with the latter report, and it is likely that the discrepancy in reports on surface CD22 expression in precursor-B ALL is due to technical and reagent differences between laboratories.…”
Section: Discussionsupporting
confidence: 84%
“…Cytoplasmic CD22 was a better marker than surface CD22 expression, which was generally weaker and on a lower proportion of cells. Other investigators have reported contradictory results of surface membrane labeling of CD22 in precursor-B ALL, ranging from negative to positive in the majority (4,8). Our results are more in keeping with the latter report, and it is likely that the discrepancy in reports on surface CD22 expression in precursor-B ALL is due to technical and reagent differences between laboratories.…”
Section: Discussionsupporting
confidence: 84%
“…Detection of minimal residual disease in ALL using flow cytometry is generally considered to have a low prognostic value (Campana & Pui, 1995;Pui et al, 1993). This is in part due to the fact that the expression of differentiation antigens is not restricted to leukaemic cells but that leukaemiaassociated immunophenotypes may be present on normal cells (Hurwitz et al, 1989(Hurwitz et al, , 1992 and at an even higher incidence in regenerating bone marrow (Oelschlägel et al, 1996). Second, the sensitivity of immunological methods is generally considered to be, at best, one in 10 000 cells, which may not be sufficiently sensitive for detection of MRD in ALL.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, expression of characteristic myeloid antigens has been associated with distinct genetically defined subgroups (Borowitz et al, 1991;Griesinger et al, 1994;Lenkei et al, 1991;Ludwig et al, 1993Ludwig et al, , 1994. Other leukaemiaassociated immunophenotypes include asynchronous expression of maturational stage-associated antigens in Blineage ALL (Hurwitz et al, 1989), ectopic expressions of antigens in T-lineage ALL Campana et al, 1991), aberrant antigen expression of B-and T-lineage associated antigens in leukaemic samples of the respective other lymphoid lineage (Grü mayer et al, 1991;Uckun et al, 1989;Muraguchi et al, 1992), and loss or low expression of common surface antigens such as CD45 in B-lineage ALL (Behm et al, 1992).…”
mentioning
confidence: 99%
“…Maturation pathways of normal hematopoietic cells have been defined using light scattering properties and expression of characteristic differentiation antigens (18,19,27,28). The approach to distinguish between leukemic and normal bone marrow cells is based on the fact that leukemic cells do not necessarily exhibit antigenic features that are characteristic of their nonmalignant counterparts (14,15). Specifically, antigen combinations were regarded as leukemia associated by the following criteria: coexpression of antigens that are found on different lineages in normal hematopoietic cells, i.e., lymphoid and myeloid restricted antigens (8,17,22,25); unphysiological coexpression of immature and mature antigens within a certain differentiation lineage (CD34 and CD15 in AML, CD34 and CD22 in ALL) (15,19,27,28); lack of a n antigen that should be present during normal differentiation (lack of CD33 or CD13 on myeloblasts, lack of Leu-M3 expression on MY-4 positive monocytes, HLA-DR negative myeloblastsimonocytes) (24,(27)(28)(29); and immunophenotypes that are absent or exceedingly rare in normal bone marrow (coexpression of TdT and early T-cell antigens, e.g., CD5, coexpression of TdT, and CD33iCD13) (1,131.…”
mentioning
confidence: 99%